2021
DOI: 10.1002/jsfa.11033
|View full text |Cite
|
Sign up to set email alerts
|

Controlled root‐zone temperature effect on baby leaf vegetables yield and quality in a floating system under mild and extreme weather conditions

Abstract: BACKGROUND A floating system is a suitable low‐cost hydroponic method for growing baby leaf vegetables. Among other, an important characteristic of the system is the use of large volume of nutrient solution which is characterized by high heat capacity. The aim of this study was to evaluate the effect of different root‐zone temperatures on baby leaves of lettuce and rocket plants grown in a floating system under mild (spring) or extreme environmental conditions (summer and winter). RESULTS Root‐zone temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Transpiration rate values were similar in both 5 and 10% liquid digestate treatments, and significantly higher than control and both 20% liquid digestate treatments for baby lettuce (Figure 4b). Slightly higher transpiration rates were reported by Karnoutsos et al [11] for non-heated cultivation in Hoagland solution during the winter season. Stomatal conductance did not show any significant difference in baby lettuce plants except for the treatment with 20% liquid digestate, with or without pH adjustment (Figure 4c).…”
Section: Quantitative Characteristics Of Baby Leaf Lettucementioning
confidence: 68%
See 1 more Smart Citation
“…Transpiration rate values were similar in both 5 and 10% liquid digestate treatments, and significantly higher than control and both 20% liquid digestate treatments for baby lettuce (Figure 4b). Slightly higher transpiration rates were reported by Karnoutsos et al [11] for non-heated cultivation in Hoagland solution during the winter season. Stomatal conductance did not show any significant difference in baby lettuce plants except for the treatment with 20% liquid digestate, with or without pH adjustment (Figure 4c).…”
Section: Quantitative Characteristics Of Baby Leaf Lettucementioning
confidence: 68%
“…For the above reasons, floating hydroponic systems are gaining increased attention today for the production of leafy vegetables. Floating systems are among the most simple, convenient, and low-cost hydroponic methods used for the production of high-quality baby leaf vegetables [10,11]. Moreover, when applying floating hydroponic techniques, the end products are cleaner, without substrate traces [12].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature inside the tanks was measured by PT−100 type sensors (Resistance thermometer Pt100, Uteco SA, Athens, Greece). More details can be found in [ 42 ]. An RZT of 22 °C is considered root-zone heating.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a root-zone temperature (RZT) of 20 °C was found to be appropriate for yield, high photosynthetic rate, and high mineral concentrations in rocket, even though the concentration of plant metabolites was not as high [ 41 ]. We have recently found that the management of RZT conditions leads to higher yields, making root temperature a useful tool for the increase in productivity of rocket [ 42 ]. However, during winter, the preservation of optimal RZT is achieved with the use of fossil fuels, which are expensive and have a high environmental impact, in Mediterranean greenhouses.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the first true leaf formation, trays were thinned up to one plant per cell, and afterwards, they were placed in two metallic tanks (2 m length × 0.8 m width × 0.24 m height) per crop, filled with 200 L Hoagland solution (100% strength) each [20]. In both tanks of each crop, pH was constantly adjusted to 6.8 ± 0.3, electrical conductivity (EC) was constantly adjusted to 2.8 ± 0.3 mS/cm, while water temperature was fluctuating between 6 and 15 • C. Rocket and lettuce baby leaves were reported to have optimum production at 20 • C root zone temperature [21]. Therefore, 6-15 • C falls within the favorable root zone temperatures, while they are typical for the experiment's period.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%